Management of Posterior Fossa Dissecting Aneurysms - Winston Chong, W. K. (Centauro S.r.l., 2008)
Treatment and prognosis of 14 patients of posterior fossa arterial dissections (AD) and dissecting aneurysms (DA) in one institution was reviewed. Internal trapping of aneurysm was performed for six patients presenting with SAH (three Vertebral, one posterior cerebral, one posterior inferior cerebellar, one anterior inferior cerebellar DA). The patency of the parent arteries was preserved in four DA patients with SAH (two Vertebral, two Basilar DA), 1 incidental vertebral DA, and one DA patient with brainstem infarction using stents and coils (four patients) or coils only (two patient). Proximal occlusion of parent artery was performed in a vertebral DA with SAH. One patient with a superior cerebellar DA presented with a midbrain infarct developed SAH with spontaneous occlusion of the aneurysm two weeks later. Of the 14 cases, ten were angiographically stable or cured during a follow up period of four to 70 months. one spontaneously resolved and two recurred. There was one death.